Kinematics/dynamics analysis of novel 3UPUR ++ SP-type hybrid hand with three flexible fingers. Issue 2 (January 2018) - Lu, Yi; Wang, Peng; Ye, Nijia
Abstract A novel 3UPUR + + SP-type hybrid hand with three flexible fingers is designed. Its prototype is built up, and its characteristics, DoF and constrained wrench are analyzed. Its kinematic formulae for solving DoF, the displacement, velocity, acceleration of the moving links are derived and analyzed. Its dynamic formulae for solving the dynamic active forces and the dynamic constrained wrench are derived. Finally, an analytic example is given to demonstrate the solution of the kinematics and dynamics, and the analytical solutions are verified by simulation model. This paper is aimed at laying a solid theoretical and technical foundation of development of the novel hybrid hand with three flexible fingers and similar hybrid hands with multi-flexible fingers.